BABA-Primed Histone Modifications in Potato for Intergenerational Resistance to Phytophthora infestans - Meller, Barbara; Kuźnicki, Daniel; Arasimowicz-Jelonek, Magdalena; Deckert, Joanna; Floryszak-Wieczorek, Jolanta (Frontiers in Plant Science, 2018)
In this paper we analyzed β-aminobutyric acid (BABA)-primed epigenetic adjustment of potato cv. ‘Sarpo Mira’ to Phytophthora infestans. The first stress-free generation of the potato genotype obtained from BABA-primed parent plants via tubers and seeds showed pronounced resistance to the pathogen, which was tuned with the transcriptional memory of SA-responsive genes. During the early priming phase before the triggering stress, we found robust bistable deposition of histone marks (H3K4me2 and H3K27me3) on the NPR1 (Nonexpressor of PR genes) and the SNI1 gene (Suppressor of NPR1, Inducible), in which transcription antagonized silencing. Switchable chromatin states of these adverse SAR regulators probably reprogrammed responsiveness of the PR1 and PR2 genes and contributed to stress imprinting. The elevated levels of heritable H3K4me2 tag in the absence of transcription on SA-dependent genes in BABA-primed (F0) and its vegetative and generative progeny (F1) before pathogen challenge provided evidence for the epigenetic mark for intergenerational memory in potato. Moreover, our study revealed that histone acetylation was not critical for maintaining BABA-primed defense information until the plants were triggered with the virulent pathogen when rapid and boosted PRs gene expression probably required HAT (histone acetyltransferase) activity both in F0 and F1 progeny.